Blood values of the Chaco chatter parrot (Amazona aestiva xanthopteryx) adult, in captivity at La Esmeralda Rescue Center in the province of Santa Fe, Argentina - Sciabarrasi, Antonio (2019)
Amazona aestiva xanthopteryx commonly known as Chaco chatter parrot, yellow-winged amazon or Argentine amazon. Its population is distributed in Argentina from the phytogeographic district of the Selva Pedemontana of the Yungas phytogeographic region and the areas near the districts of Western Chaco, Arid and Serrano. In that country it is one of the parrots most illegally trafficked. The basic aspects of clinical pathology, which include hematology, have been commonly used in the diagnosis of diseased birds; however, it is necessary to know the physiological parameters taking into account the variables relevant to each region and their respective conditions. The aim of the present study was to describe the values ​​obtained for erythrocytes, Hematocrit (Hct), Hemoglobin (Hb), Mean Corpuscular Volume (MCV), Middle Corpuscular Hemoglobin (MCH), Concentration of Middle Corpuscular Hemoglobin (MCH), absolute and differential counting of leukocytes and absolute platelet count of an apparently healthy population of 27 captive individuals belonging to this subspecies, located in the Center of Rescue, Rehabilitation and Relocation of La Esmeralda Fauna of the Province of Santa Fe in Argentina. The data obtained were tabulated and analyzed by descriptive statistics. The results for the different parameters were mostly similar to those reported for other Psittaciformes birds, with minimal differences associated with the different environmental and management conditions of each study. The values obtained from the talking parrot of the Chaco will be a guide for the application in the clinic and rescue programs, conservation.